Domoic Acid Variations in Response to Environmental Conditions in an Eutrophic Estuary, Golden Horn (Turkey) - YURDUN, TÜRKAN (CENTRAL FISHERIES RESEARCH INST, 2017)
Particulate domoic acid (pDA) concentrations, Pseudo-nitzschia abundances and their relationship with environmental variables were investigated from August 2011 to July 2012 in the Golden Horn Estuary (GHE), Turkey. To determine the distribution of pDA concentrations, the high performance liquid chromatography - fluoresence detection (HPLC-FLD) method was used (detection limit 0.2 mu g mL(-1)). pDA concentrations ranged from 0.24 to 21.03 mu g mL(-1) and the highest value was measured at FD3 station, located in the middle estuary, in May 2012. pDA levels were undetectable between Aug. 2011 and March 2012 period in all stations, except in Nov. 2011 (0.83 mu g mL(-1), at FD3 station). pDA values reached the maximum value when Pseudo-nitzschia abundance was counted at the highest level (1968103 cells L-1, at FD3 station). The relationship between pDA and environmental parameters was investigated by Spearman correlation analysis and the influencing factors of the pDA distribution were evaluated with Principal Component Analysis (PCA). According to the results, pDA production is mostly controlled by temperature, SiO2 and NO3+NO2. This study reports the first results of DA in the GHE and these results may be used to consider the probability of fmding similar conditions in the Turkish seas.
Keywords: Domoic acid; Pseudo-nitzschia; HPLC; Golden Horn Estuary; DIATOM NITZSCHIA-PUNGENS; GULF-OF-MEXICO; PSEUDO-NITZSCHIA; MONTEREY BAY; CALIFORNIA; SEA; PHYTOPLANKTON; ABUNDANCE; SHELLFISH; CHANNEL